REVIEW OF GOOD CORPORATE GOVERNANCE (GCG) APPLICATION IN OPERATIONAL ACTIVITIES IN PT BANK CENTRAL ASIA, Tbk - Mesra Lindawati (Dinasti International Journal of Education Management And Social Science, 2020)
The need to apply the principles of good corporate governance in companies felt very strong in the industrial banking. External and internal conditions in banking are getting more complex. The risks of banking business activities are more diverse. Given the situation, the need of healthy company practices in the banking field. Increases. BCA is a banking financial services company that was established with the aim to participate in advancing the Indonesian economy. As a banking financial services company that relies on customer trust, the management of the company carries out operations with the principle of prudence. One of the keys made by PT Bank Central Asia, Tbk to face the increasingly stringent challenges of the Indonesian banking sector is to carry out good corporate governance. This is done so that the Bank can consistently maintain customers, shareholders, and other parties trust.